Dietary Supplements Use among Medical Students of Bangladesh - Johora, Fatema; Ghosh, Satabdi; Ferdoush, Jannatul; Abbasy, Asma Akter; Ahmed, Tarafder Shahniam; Ferdous, Asiya; Jeenia, Fatiha Tasmin; Sabiha, Kazi; Shirin, Mst Arifa; Mahboob, Sabiha; et al. (Bangladesh Journal of Medical Education, 2025)
Introduction: The use of dietary supplements (DS) is increasing globally. Intense debate surrounds the benefits of individual high-dose micronutrient supplementation among well-nourished individuals. Demographic and lifestyle factors such as monthly income, educational status, sedentary lifestyle and smoking status were reported to correlate with dietary supplement use. Dietary supplement use among medical students is of particular research interest as they are the future prescribers. Objective: To find out the prevalence and associated factors of DS use among the medical students. Materials and Methods: This descriptive cross-sectional study was conducted in the Department of Pharmacology & Therapeutics of 18 medical colleges of Bangladesh including both government and non-government medical colleges. A structurred questionnaire survey was conducted among the 3rd year and 4th year MBBS students of studied medical colleges who agreed to participate the study, and total 2629 medical students participated in this study. Results: The overall prevalence of DS use was 39.25%. The mostused DS were Vitamin C (31.41%) and multivitamins-minerals (24.92%). In 34.30% cases, DS were recommended by physician. Academic knowledge (58.72%) was the most common source of information, followed by prior experience (44.08%). The most common reason for taking DS was for improvement of overall health (41.47%). Supplement intake was significantly associated with gender (p = 0.015), marital status (p = 0.007), nationality (p = <0.00001) and types of medical colleges (p =0.032). Female students (41.00%), married (50.38%), foreign nationality (49.52%) and students studying in government medical colleges (41.00%) took significantly more DS. Conclusion: The prevalence of supplement use was among medical students was similar to values reported previously in the literature. It would be better to review the undergraduate medical education in regards of DS for encouraging better and safer prescribing of supplements in future. BJME, Volume-16, Issue-02, July 2025: 101-114